TRANFORMASI BERKELANJUTAN LITERASI ANAK MELALUI PENELITIAN TINDAKAN PARTISIPATIF DI PEDESAAN PAMEKASAN - Rofiqi (CV. Jendela Gagasan, 2024)
Literacy is a basic skill that determines the success of children's education in the future. This study aims to improve the literacy skills of children in Tebul Barat Village through a Participatory Action Research (PAR) approach. The program was implemented at SDN Tebul Barat, Pegantenan District, Pamekasan Regency for 30 days, involving students in grades 4-6 as the main target. The PAR method was chosen to ensure the active participation of all stakeholders in the process of identifying problems, planning, implementing, and evaluating the program. The main activities included a 15-minute GEMA BACA (Reading Movement) habit, the development of a literacy corner, interactive storytelling, and intensive mentoring. The results of the study showed an increase in reading skills, reading comprehension, and students' interest in reading, as well as the formation of a sustainable school literacy culture. This program created a participatory literacy ecosystem that involved students, teachers, parents, and the community as agents of change. The novelty of this research lies in the integration of the PAR approach with elementary school literacy programs in the Indonesian rural context, which proved to be effective in improving not only technical literacy skills but also building social capital for program sustainability.